2013
DOI: 10.1377/hlthaff.2012.1252
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Cost Containment Strategies Used In Four Other High-Income Countries Hold Lessons For The United States

Abstract: Around the world, rising health care costs are claiming a larger share of national budgets. This article reviews strategies developed to contain costs in health systems in Canada, England, France, and Germany in 2000-10. We used a comprehensive analysis of health systems and reforms in each country, compiled by the European Observatory on Health Systems and Policies. These countries rely on a number of budget and price-setting mechanisms to contain health care costs. Our review revealed trends in all four coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 8 publications
0
56
0
6
Order By: Relevance
“…A final implication of this study is that attaining financial protection on par with that achieved in France will require more comprehensive income-based limits on OOP spending than currently exist in most countries. However, the magnitude of financial risk revealed here may indicate a more general need to shift from cost-sharing measures as a way to reduce health care costs, and toward alternative policy mechanisms such as are being attempted in many other countries [31]. …”
Section: Discussionmentioning
confidence: 93%
“…A final implication of this study is that attaining financial protection on par with that achieved in France will require more comprehensive income-based limits on OOP spending than currently exist in most countries. However, the magnitude of financial risk revealed here may indicate a more general need to shift from cost-sharing measures as a way to reduce health care costs, and toward alternative policy mechanisms such as are being attempted in many other countries [31]. …”
Section: Discussionmentioning
confidence: 93%
“…However, the authors note that part of the reason for the small behavioral response found here may be that the policy was either not applicable or not binding for many users, limiting the potential for savings. There is some evidence of movement towards strategies that promote efficiency through value-based cost sharing (using cost sharing to encourage patients to use medication, services, and providers that offer better value than other options) rather than simply applying user fees across the board (Stabile et al 2013).…”
Section: Cost Sharing and User Feesmentioning
confidence: 99%
“…It has been able to accomplish cost containment mainly through a tightly controlled nationally uniform schedule set by the government (Hashimoto, et al, 2011). Other countries such as Canada, the UK, France, and Germany have also used budget and price controls as a method of healthcare cost containment with differing degrees of effectiveness (Stabile, et al, 2013).…”
mentioning
confidence: 99%